Sweet syndrome with bitter outcomes in cervical cancer: A case report - Kelly Lamiman; Justine Sheu; Brandon Goodwin; Sandra Hatch; Gwyn Richardson (Elsevier, 2021)
Background: Sweet Syndrome, or acute febrile neutrophilic dermatosis, is a non-infectious, painful rash accompanied by fever, leukocytosis and skin biopsy showing neutrophilic dermal inflammation. It is either idiopathic, drug-induced or malignancy associated (MASS). MASS is uncommon in cervical cancer, and usually signals diagnosis, progression or recurrence. Clinical Course: Two months following chemoradiation for stage IIIC2(r) squamous cell carcinoma (SCC) of the cervix, a 55-year-old female developed painful papules and plaques on her left toes. One week later she developed fever and the rash spread to her body. Labs revealed leukopenia and an elevated erythrocyte sedimentation rate. Punch biopsy showed neutrophilic dermal inflammation with papillary dermal edema and was negative for infectious immunohistochemistry. The clinical presentation and histopathological features were consistent with, and met diagnostic criteria for Sweet Syndrome. One month following Sweet Syndrome diagnosis and four months following chemoradiation, positron emission tomography scan revealed recurrence in the pelvic lymph nodes. At this time, she had residual rash on her thighs that responded to oral methylprednisolone. She declined further chemotherapy for recurrent SCC and opted for palliative care. Conclusion: We present a rare case of MASS in cervical cancer associated with recurrence two months after chemoradiation.